2011
DOI: 10.2174/1874398601104010071
|View full text |Cite
|
Sign up to set email alerts
|

Realized Gains from Planting Pinus taeda in 6.1 Meter Rows in Alabama

Abstract: Pinus taeda L. plantations in the United States are typically established using rows that are spaced 3 to 4 m apart. Although one company now plants pines in 6.1 m rows, reports on performance using this row spacing are rare. This paper provides a case study (established at the Solon Dixon Forestry Education Center) that compares two densities [672 vs 1344 seedlings per ha (SPH)] when fixing the between-row distance to 6.1 m and using either 2.44 m or 1.22 m within-row distances between the planted trees. At a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…One was located in the Piedmont plateau region and the other in the Coastal Plain of Alabama. Growth and yield for the BTR and TMR were simulated using the PTAEDA 4.0 growth model (Burkhart et al, 2008), which has been shown to produce reliable results for both young stands (Kantavichai et al, 2014) and rotation age stands (South et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…One was located in the Piedmont plateau region and the other in the Coastal Plain of Alabama. Growth and yield for the BTR and TMR were simulated using the PTAEDA 4.0 growth model (Burkhart et al, 2008), which has been shown to produce reliable results for both young stands (Kantavichai et al, 2014) and rotation age stands (South et al, 2011).…”
Section: Methodsmentioning
confidence: 99%